Paris, capital of modernity - Harvey, David, 1935- (Routledge, 2003)
Collecting David Harvey's finest writings on 19th century Paris, this title offers insights ranging from the birth of consumerist spectacle on the Parisian boulevards, the creative visions of Balzac, Baudelaire and Zola, and the reactionary cultural politics of the bombastic Sacre Coeur.